Growth Mechanism and Field Emission Characteristics of GaO/GaN Nanotips Using Iodine-assisted Enhanced Focused Ion Beam Etching - Hu, Zhan-Shuo; Hung, Fei-Yi; Chang, Shoou-Jinn; Huang, Bohr-Ran; Lin, Bo-Cheng; Chen, Kuan-Jen; Chen, Tse-Pu; Hsu, Wen-I (Current Nanoscience, 2011)
GaN nanorods are fabricated with an AgO mask by a process of iodine-assisted focused ion beam etching (IFIBE). The transformation from GaN nanorod to GaN nanotip structure, the thermal treatment uses a high temperature of 800° C in air to increase the partial oxygen pressure resulting in the formation of a double mask, GaO and AgO. In addition, the Ag clusters react with the iodine gas to affect the etching rate and retain a GaO zone on the GaN nanotip arrays. Oxide-capped GaN nanotips can be applied as field emitter. The turn-on electric field was 2.2V/um when the current density was 0.1mA/cm2.
Keywords: Etching Mechanism